Parenteral nutrition impairs plasma bile acid and gut hormone responses to mixed meal testing in lean healthy men. Issue 3 (March 2021) - Meessen, Emma C.E.; Bakker, Guido J.; Nieuwdorp, Max; Dallinga-Thie, Geesje M.; Kemper, E. Marleen; Olde Damink, Steven W.; Romijn, Johannes A.; Hartmann, Bolette; Holst, Jens J.; Knop, Filip K.; Groen, Albert K.; Schaap, Frank G.; et al.
Summary: Background & aims: To investigate the acute effects of intravenous vs enteral meal administration on circulating bile acid and gut hormone responses. Methods: In a randomized crossover design, we compared the effects of duodenal (via a nasoduodenal tube) vs parenteral (intravenous) administration over 180 min of identical mixed meals on circulating bile acid and gut hormone concentrations in eight healthy lean men. We analysed the bile acid and gut hormone responses in two periods: the intraprandial period from time point (T) 0 until T180 during meal administration and the postprandial period from T180 until T360, after discontinuation of meal administration. Results: Intravenous meal administration decreased the intraprandial (AUC (μmol/L∗min) duodenal 1469 ± 284 vs intravenous 240 ± 39, p < 0.01) and postprandial bile acid response (985 ± 240 vs 223 ± 5, p < 0.05) and was accompanied by decreased gut hormone responses including glucose-dependent insulinotropic polypeptide, glucagon-like peptide 1, glucagon-like peptide 2 and fibroblast growth factor 19. Furthermore, intravenous meal administration elicited greater glucose concentrations, but similar insulin concentrations compared to enteral administration. Conclusions: Compared to enteral administration, parenteral nutrition results in lower postprandial bile acid and gut hormone responses in healthy lean men. This was accompanied by higher glucose concentrations in the face of similar insulin concentrations exposing a clear incretin effect of enteral mixed meal administration. The alterations in bile acid homeostasis were apparent after only one intravenous meal. Highlights: Intravenous meal infusion impairs normal bile acid responses in healthy lean men. Intravenous meal infusion impairs normal gut hormone responses in healthy lean men. The alterations in bile acids were apparent after only one intravenous meal. Importance of enteral nutritional strategies to maintain circulating bile acids.